2007
DOI: 10.1093/icesjms/fsm150
|View full text |Cite
|
Sign up to set email alerts
|

Escape mortality of cod, saithe, and haddock in a Barents Sea trawl fishery

Abstract: Ingólfsson, Ó. A., Soldal, A. V., Huse, I., and Breen, M. 2007. Escape mortality of cod, saithe, and haddock in a Barents Sea trawl fishery. – ICES Journal of Marine Science, 64: 000–000. We investigated the survival of gadoid fish in the Barents Sea escaping from a demersal trawl during commercial fishing conditions, with and without a sorting grid, at high and low levels of fishing intensity. The mortality of cod and saithe was negligible and unrelated to experimental conditions. Haddock mortality was genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
60
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 17 publications
5
60
1
Order By: Relevance
“…(Ryer et al 2004) like brown comber in the present study. Ingólfsson et al (2007) also reported such differences of mortality among three fish species that although cod and saithe (Pollachius virens) were capable of surviving after their escape from the trawl, haddock was more vulnerable. It was clear that brown comber have high capability of surviving after escape from the cod-ends.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…(Ryer et al 2004) like brown comber in the present study. Ingólfsson et al (2007) also reported such differences of mortality among three fish species that although cod and saithe (Pollachius virens) were capable of surviving after their escape from the trawl, haddock was more vulnerable. It was clear that brown comber have high capability of surviving after escape from the cod-ends.…”
Section: Discussionmentioning
confidence: 90%
“…Improving the selectivity of fishing gear to reduce the bycatch and discards has been one of the main management tools for sustainable fisheries (Tosunoğlu 2003a, Suuronen 2005, Ingólfsson et al 2007). Although in trawl fishery it is allowed that considerable amount of fish escape passing through trawl cod-ends, the process will only work effectively if escaping fish could survive (Breen 2004, Suuronen 2005.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations